2016
DOI: 10.1140/epjds/s13688-016-0069-1
|View full text |Cite
|
Sign up to set email alerts
|

Technological novelty profile and invention’s future impact

Abstract: We consider inventions as novel combinations of existing technological capabilities. Patent data allow us to explicitly identify such combinatorial processes in invention activities (Youn et al. in J R Soc Interface 12:20150272, 2015). Unconsidered in the previous research, not every new combination is novel to the same extent. Some combinations are naturally anticipated based on patent activities in the past or mere random choices, and some appear to deviate exceptionally from existing invention pathways. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 46 publications
(57 reference statements)
1
36
0
2
Order By: Relevance
“…The highest-impact science is primarily grounded in conventional combinations of prior work, yet it simultaneously features unusual combinations (2527). Papers of this type are twice as likely to receive high citations (26).…”
Section: Noveltymentioning
confidence: 99%
“…The highest-impact science is primarily grounded in conventional combinations of prior work, yet it simultaneously features unusual combinations (2527). Papers of this type are twice as likely to receive high citations (26).…”
Section: Noveltymentioning
confidence: 99%
“…In order to compute the novelty of a creative work, we first consider the fact that any new creative work-be it a scientific paper, a technological patent, or a musical compositioncontains the familiar, 'conventional' elements that can be found in known older works, and the unfamiliar, 'novel' elements that have not [4,7,8]. Intuitively then a work that features a larger novel-to-conventional ratio of elements could be considered more novel, and vice versa.…”
Section: Model and Formalismmentioning
confidence: 99%
“…found their innate preference for new stimuli [5,6]; and second, data-driven studies on citation networks and impacts of scientific papers and patents have shown that novelty is often a key feature in influential scientific knowledge and technological systems [7,8]. This is also true in cultural creations such as music, where continual experimentations of musical elements (e.g.…”
mentioning
confidence: 99%
“…The authors find that the rate of new technological capabilities is slowing down but a huge number of combinations allows for a "practically infinite space of technological configurations". By considering technology as a combinatorial process, [25] uses USPTO data to investigate the extent of novelty in patents. They propose a likelihood model for assessing the novelty of combinations of patent codes.…”
Section: Modularity and Hierarchymentioning
confidence: 99%